Efek Pemberian Minyak Zaitun (Olive oil) Terhadap Perubahan Profil Lipid Pada Tikus putih (Rattus novergicus) - Syamsu, Rachmat Faisal (Jurnal Ilmiah As-Syifaa, 2017)
This research aims to know  the effects of olive oil  to changes profil lipid (total cholesterol, LDL, HDL, and triglycerides)  in the blood of the Rattus novergicus who were given a  high cholesterol diet. This research is experimental research methods laboratory with pre and post test control . Homogeneous data and normal data  next performed a test of paired t-Test and LSD test.  All test data using the 95% significance level (p = 0.05).  Conclusion of this research is the olive oil was able to lower the lipid profile, cholesterol 22,61%, LDL 38,48%, triglycerides 17.61% and increase the HDL 25.32%  in the blood of rats high cholesterol diet